Eksperymenty nad tożsamością płciową mężczyzn w twórczości Marka Hłaski - Mosak, Piotr (Śląskie Studia Polonistyczne, 2020)
The present article aims to analyse the depictions of male protagonists in the oeuvre of Marek Hłasko. The post-World War Two crisis of hegemonic masculinity resulted in transformations of male and female gender identities in the 1950s. What seems to reflect the said reconfiguration of masculinity model are the changes occurring between the main protagonists of the particular pieces of Hłasko’s prose. In the 1954 short story entitled Baza Sokołowska, the men’s identities are, in the natural way, embedded in biology. In order to join the male community of drivers and gain their respect, it is enough to go through an initiation ritual. In the prose written by Hłasko after 1955, however, more and more often appear the male characters who humiliate the young and thwart them on their way to join masculine community, yet simultaneously some characters are presented who contest forms of patriarchal culture and refuse to participate in it. Hłasko’s Israeli novels, in turn, feature a series of male protagonists for whom gender (or even sexual) identity is merely a social construct. The narrator/protagonist of Drugie zabicie psa (Killing the Second Dog) would even consciously “perform” his masculinity to obtain an affluent female tourist’s trust and, as a result, to cozen her out of her money, which he needs to pay back his debts. The analysis of Marek Hłasko’s selected prose writings focused on the representation of various masculinity models leads the author of the article to a conclusion that male gender identity is consistently shifting towards constructivist concepts.